Representation or participation? - Larsson, Anders Olof (Javnost (Ljubljana), 2013)
The uses of the popular microblogging service Twitter for political purposes have been discussed by scholars and political pundits alike. While suggestions have been made that the conversational aspects of the microblog could serve to instigate online deliberation between equals, rather few studies have investigated such claims empirically. This paper presents such an empirical study, based on a large-scale data set of tweets concerning the 2011 Danish parliamentary election. By combining state-of-the-art data collection and analysis techniques with theoretically informed matters for discussion, we provide an assessment of political Twitter activity among high-end users of the microblog during a one-month period leading up to the election. Identifying a series of user types, findings indicate that while the bulk of the studied activity bares characteristics of a representative public sphere, traces of a participatory public sphere were also discerned.
Keywords: Danska; Denmark; election; volitve; politična kampanja; politična propaganda; družbena omrežja